Electrolyte for lithium metal battery as well as preparation method and application of electrolyte
By adding carbon-carbon double bonds or carbon-carbon triple bonds as bridged Gemini quaternary ammonium salts to the electrolyte of lithium metal batteries, the problem of interface instability caused by lithium dendrites is solved, and the growth of lithium metal batteries is achieved Improved cycle stability and safety.
Patent Information
- Application Number
- CN202411454207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
AI Technical Summary
Lithium metal batteries are prone to form lithium dendrites during the electrochemical "nucleation-deposition-growth" process, resulting in interface instability and affecting the cyclic stability and safety of the battery.
Gemini quaternary ammonium salt containing carbon-carbon double bonds or carbon-carbon triple bonds as bridge groups is used as additives, and added to the electrolyte of lithium metal batteries. By adsorbing on the surface of dendrites, the mass transfer process of lithium ions is blocked, thereby inhibiting lithium Dentite growth.
Significantly inhibit the growth of lithium dendrites, improve the cycle life and battery capacity of lithium metal batteries, and enhance the safety and stability of the battery.
Smart Images

Figure CN119400953A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrolyte for a lithium metal battery and a preparation method and application thereof, belonging to the technical field of lithium metal batteries, and in particular to a Gemini quaternary ammonium salt additive having a carbon-carbon double bond or a carbon-carbon triple bond as a bridging group for use in a lithium metal battery electrolyte. Background Art
[0002] The input of clean and renewable energy, such as solar energy, tidal energy, wind energy and hydropower, has improved the social energy structure. However, these clean energy sources are difficult to store and energy conversion is not easy to achieve, which seriously hinders their large-scale application. Developing high-energy-density, long-life, and high-safety energy storage battery technology is an important way to support the development of renewable energy. At present, the specific energy provided by the lithium-ion battery system is limited and can no longer meet people's needs. The construction of a new type of lithium metal battery has become an effective means to improve energy density and an important research direction.
[0003] However, due to the irregular growth of lithium dendrites and serious interface side reactions, lithium metal anodes are prone to form lithium dendrites during the electrochemical "nucleation-deposition-growth" process, inducing unfavorable factors such as passivation film rupture, volume expansion, electrolyte drying, formation of dead lithium, and dendrite piercing the diaphragm, which destroys the interface stability. The unstable interface hinders the mass transfer and nuclear transfer process, causing rapid capacity decay of the lithium metal anode, increased interface resistance, internal short circuit, thermal runaway and other safety issues, resulting in many challenges for lithium metal anodes in practical applications.
[0004] So far, researchers have proposed a variety of strategies to solve the above problems encountered by lithium metal batteries, including lithium negative electrode structure design, solid-liquid interface design, solid electrolyte and electrolyte optimization and modification methods, which effectively reduce the negative impact of dendrite growth. Among them, electrolyte optimization and modification are mainly used to improve battery performance, especially to extend life, improve safety and stability. Electrolyte optimization and modification can effectively promote the formation of stable SEI, thereby significantly inhibiting the growth of lithium dendrites, thereby enhancing the cycle stability of the battery and improving its working efficiency. At the same time, inhibiting dendrite growth from the perspective of electrolyte optimization and modification is also the most convenient and most conducive strategy for market development in terms of technology. Summary of the invention
[0005] In view of the above-mentioned deficiencies of current lithium metal batteries, the purpose of the present invention is to provide an electrolyte for lithium metal batteries and a preparation method and application thereof, so as to effectively solve the problem of lithium dendrites in existing lithium metal batteries.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0007] An electrolyte for a lithium metal battery, the electrolyte comprising an organic solvent, a soluble lithium salt and an additive;
[0008] The organic solvent is at least one of 1,3-dioxolane, ethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate and ethyl butyrate;
[0009] The soluble lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium bis(oxalatoborate);
[0010] The additive is a Gemini quaternary ammonium salt with a carbon-carbon double bond or a carbon-carbon triple bond as a bridging group, specifically at least one of the following compounds: ethylene alkyl (R2 alkyl ammonium fluoride), ethylene alkynyl (R3 alkyl ammonium fluoride), ethylene alkyl (R4 alkyl ammonium chloride), ethylene alkynyl (R5 alkyl ammonium chloride), ethylene alkyl (R6 alkyl ammonium bromide), ethylene alkynyl (R7 alkyl ammonium bromide), ethylene alkyl (R8 alkyl ammonium iodide), ethylene alkynyl (R9 alkyl ammonium iodide), wherein the R2 alkyl group corresponds to a hydrocarbon group with 1 to 30 carbon atoms, preferably a hydrocarbon group with 16 to 20 carbon atoms;
[0011] The structural formula of ethylene alkyl (R alkyl ammonium fluoride) is:
[0012]
[0013] The structural formula of ethylene alkynyl (R alkyl ammonium fluoride) is:
[0014]
[0015] The structural formula of ethylene (R alkyl ammonium chloride) is:
[0016] The structural formula of ethylene alkynyl (R alkyl ammonium chloride) is:
[0017] The structural formula of ethylene alkyl ammonium bromide is:
[0018] The structural formula of ethylene alkynyl (R alkyl ammonium bromide) is:
[0019] The structural formula of ethylene alkyl (R alkyl ammonium iodide) is:
[0020] The structural formula of ethylene alkynyl (R alkyl ammonium iodide) is:
[0021]
[0022] Wherein, R is a hydrocarbon group having 1 to 30 carbon atoms;
[0023] In the electrolyte, the molar concentration of soluble lithium salt is 1 mol / L;
[0024] In the electrolyte, the molar concentration of the additive is 1-20 mmol / L, preferably 5 mmol / L.
[0025] A method for preparing an electrolyte for a lithium metal battery, comprising mixing an organic solvent, a soluble lithium salt and an additive to obtain an electrolyte;
[0026] The invention discloses an application of an electrolyte for a lithium metal battery. The electrolyte is matched with a positive electrode, a negative electrode and a separator to assemble a lithium metal battery. The obtained lithium metal battery has excellent cycle life and battery capacity.
[0027] The negative electrode is a lithium sheet, lithium foil or lithium powder, preferably a lithium sheet with a thickness of 0.5 mm;
[0028] The positive electrode material is sulfur, LiCoO2, LiNiO2, LiMn2O4, LiFePO4 or lithium nickel manganese oxide, preferably sulfur;
[0029] The membrane material is glass fiber, polyethylene or polypropylene, preferably polypropylene.
[0030] Beneficial Effects
[0031] (1) The present invention uses a Gemini quaternary ammonium salt additive containing a bridging group of a carbon-carbon double bond or a carbon-carbon triple bond. The additive molecule can be adsorbed on the surface of the dendrite, blocking the mass transfer process of lithium ions, thereby significantly inhibiting the growth of lithium dendrites.
[0032] (2) The present invention uses a Gemini quaternary ammonium salt additive containing a bridging group of a carbon-carbon double bond or a carbon-carbon triple bond, which can significantly improve the cycle performance of the Li||Li symmetric battery and reduce the deposition overpotential.
[0033] (3) The present invention uses a Gemini quaternary ammonium salt additive containing a bridging group of a carbon-carbon double bond or a carbon-carbon triple bond, which can significantly improve the coulombic efficiency of the Li||Cu half-cell and reduce the deposition overpotential.
[0034] (4) The present invention uses a Gemini quaternary ammonium salt additive containing a bridging group of a carbon-carbon double bond or a carbon-carbon triple bond, which can significantly improve the specific capacity and capacity retention rate of the Li||S full battery, while also improving the cycle life.
[0035] (5) The equipment and reagents used in the present invention are easily available, safe, non-toxic, and environmentally friendly. The preparation method of the modified electrolyte is simple and easy to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The Li||Li symmetric battery in Example 1 and the comparative example at a current density of 1 mA cm -2 , surface capacity is 1mAhcm -2 Cyclic performance diagram under conditions;
[0037] Figure 2 The Li||Li symmetric battery in Example 1 and the comparative example at a current density of 5 mA cm -2 、Surface capacity is 5mAhcm -2 Cyclic performance diagram under conditions;
[0038] Figure 3 The Li||Li symmetric battery in Example 1 and the comparative example at a current density of 10 mA cm -2 , surface capacity is 10 mAh cm -2 Cyclic performance diagram under conditions;
[0039] Figure 4 The Li||Li symmetric battery in Example 1 and the comparative example at a current density of 100 mA cm -2 , surface capacity is 1 mAh cm -2 Cyclic performance diagram under conditions;
[0040] Figure 5 For the Li||Li symmetric battery in Example 1 and the comparative example, the surface capacity is 1 mAh cm -2 Under the condition, the current density is 1 mA cm -2 -200mA cm -2 Symmetrical battery rate performance diagram that varies within a range of;
[0041] Figure 6 For the Li||Li symmetric battery in Example 1 and the comparative example, at a current density of 1 mA cm -2 , surface capacity is 1mAhcm -2 SEM images of the surface and side of the lithium negative electrode after cycling for 400 hours under different conditions.
[0042] Figure 7 The Li||Cu half-cell in Example 1 and the comparative example at a current density of 1 mA cm -2 , with a surface capacity of 1 mAh cm -2 Coulomb efficiency diagram under conditions;
[0043] Figure 8Graph showing the cycling performance of the Li||S full battery at 0.1C rate in Example 1 and the comparative example;
[0044] Fig. 9 This is a full battery rate performance diagram of the Li||S full battery in Example 1 and the comparative example, with the charge and discharge rate varying in the range of 0.1C-5C. DETAILED DESCRIPTION
[0045] In order to better understand the present invention, the present invention is further described below by examples, which are only used to explain the present invention. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0046] Example 1
[0047] 8.83 mg of solid ethylene hexadecyl ammonium bromide was weighed and added to 3 ml of 1.0 M LiTFSI in DME:DOL = 1:1 vol% electrolyte, and stirred thoroughly until completely dissolved to obtain a 5 mmol / L ethylene hexadecyl ammonium bromide solution, recorded as 5 mM ECAB.
[0048] The obtained 5mM ECAB was used to prepare a Li||Li symmetric battery: a CR2025 type electrode shell was used, the positive and negative electrodes were both lithium sheets (diameter 11mm), and the diaphragm was made of polypropylene (diameter 19mm). 80μL of the obtained 5mM ECAB was dripped onto the diaphragm, and the battery was assembled in the order of positive electrode shell-lithium sheet-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||Li symmetric battery.
[0049] Use the obtained 5mM ECAB to prepare a Li||Cu half-cell: use a CR2025 type electrode shell, the positive electrode is a copper foil (diameter of 11mm), the negative electrode is a lithium sheet (diameter of 11mm), and the separator is a polypropylene (diameter of 19mm). 80μL of the obtained 5mM ECAB is dripped on the separator, and the battery is assembled in the order of positive electrode shell-copper foil-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly is completed, pressurize and package to prepare a Li||Cu half-cell;
[0050] The obtained 5mM ECAB was used to prepare a Li||S full battery: a CR2025 type electrode shell was used, the positive electrode was an aluminum foil coated with sulfur (diameter 11mm), the negative electrode was a lithium sheet (diameter 11mm), and the separator was a polypropylene (diameter 19mm). 80μL of the obtained 5mM ECAB was dripped onto the separator, and the battery was assembled in the order of positive electrode shell-positive electrode-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||S full battery.
[0051] Example 2
[0052] Weigh 6.73 mg of solid ethylenediamine (eicosyl ammonium iodide) and add it to 3 ml of 1.0 M LiTFSI in DME:DOL = 1:1 vol% electrolyte, stir thoroughly until completely dissolved, and obtain a 3 mmol / L ethylenediamine (eicosyl ammonium iodide) solution, recorded as 3 mM EEAI.
[0053] The obtained 3mM EEAI was used to prepare a Li||Li symmetric battery: a CR2025 type electrode shell was used, the positive and negative electrodes were both lithium sheets (diameter 11mm), and the diaphragm was made of polypropylene (diameter 19mm). 80μL of the obtained 3mM EEAI was dripped onto the diaphragm, and the battery was assembled in the order of positive electrode shell-lithium sheet-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||Li symmetric battery.
[0054] The obtained 3mM EEAI was used to prepare a Li||Cu half-cell: a CR2025 type electrode shell was used, the positive electrode was a copper foil (diameter of 11mm), the negative electrode was a lithium sheet (diameter of 11mm), and the separator was a polypropylene (diameter of 19mm). 80μL of the obtained 3mMEEAI was dripped onto the separator, and the battery was assembled in the order of positive electrode shell-copper foil-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||Cu half-cell;
[0055] The obtained 3mM EEAI was used to prepare a Li||S full battery: a CR2025 type electrode shell was used, the positive electrode was an aluminum foil coated with sulfur (diameter 11mm), the negative electrode was a lithium sheet (diameter 11mm), and the separator was a polypropylene (diameter 19mm). 80μL of the obtained 3mM EEAI was dripped onto the separator, and the battery was assembled in the order of positive electrode shell-positive electrode-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||S full battery.
[0056] Example 3
[0057] Weigh 2.30 mg of solid ethylene alkynyl (tetradecyl ammonium chloride) and add it to 3 ml of 1.0 M LiTFSI in DME:DOL = 1:1 vol% electrolyte, stir thoroughly until completely dissolved, and obtain a 1 mmol / L ethylene alkynyl (tetradecyl ammonium chloride) solution, recorded as 1 mM ATAC.
[0058] The obtained 1mM ATAC was used to prepare a Li||Li symmetric battery: a CR2025 type electrode shell was used, the positive and negative electrodes were both lithium sheets (diameter 11mm), and the diaphragm was made of polypropylene (diameter 19mm). 80μL of the obtained 1mM ATAC was dripped onto the diaphragm, and the battery was assembled in the order of positive electrode shell-lithium sheet-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||Li symmetric battery.
[0059] Use the obtained 1mM ATAC to prepare a Li||Cu half-cell: use a CR2025 type electrode shell, a copper foil (diameter of 11mm) for the positive electrode, a lithium sheet (diameter of 11mm) for the negative electrode, and a polypropylene (diameter of 19mm) for the separator. Add 80μL of the obtained 1mM ATAC dropwise on the separator, and assemble the battery in the order of positive electrode shell-copper foil-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly is completed, pressurize and package to prepare a Li||Cu half-cell;
[0060] The obtained 1mM ATAC was used to prepare a Li||S full battery: a CR2025 type electrode shell was used, the positive electrode was an aluminum foil coated with sulfur (diameter 11mm), the negative electrode was a lithium sheet (diameter 11mm), and the separator was a polypropylene (diameter 19mm). 80μL of the obtained 1mM ATAC was dripped onto the separator, and the battery was assembled in the order of positive electrode shell-positive electrode-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||S full battery.
[0061] Example 4
[0062] Weigh 7.92 mg of solid ethylene hexadecyl ammonium fluoride and add it to 3 ml of 1.0 M LiTFSI in DME:DOL = 1:1 vol% electrolyte, stir thoroughly until completely dissolved, and obtain a 5 mmol / L ethylene hexadecyl ammonium fluoride solution, recorded as 5 mM ECAF.
[0063] The obtained 5mM ECAF was used to prepare a Li||Li symmetric battery: a CR2025 type electrode shell was used, the positive and negative electrodes were both lithium sheets (diameter 11mm), and the diaphragm was made of polypropylene (diameter 19mm). 80μL of the obtained 5mM ECAF was dripped onto the diaphragm, and the battery was assembled in the order of positive electrode shell-lithium sheet-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||Li symmetric battery.
[0064] Use the obtained 5mM ECAF to prepare Li||Cu half-cell: use CR2025 type electrode shell, the positive electrode is copper foil (diameter 11mm), the negative electrode is lithium sheet (diameter 11mm), and the separator is polypropylene (diameter 19mm). 80μL of the obtained 5mM ECAF is dripped on the separator, and the battery is assembled in the order of positive electrode shell-copper foil-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly is completed, pressurize and package to prepare Li||Cu half-cell;
[0065] The obtained 5mM ECAF was used to prepare a Li||S full battery: a CR2025 type electrode shell was used, the positive electrode was an aluminum foil coated with sulfur (diameter 11mm), the negative electrode was a lithium sheet (diameter 11mm), and the separator was a polypropylene (diameter 19mm). 80μL of the obtained 5mM ECAF was dripped onto the separator, and the battery was assembled in the order of positive electrode shell-positive electrode-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly was completed, the battery was pressurized and packaged to prepare a Li||S full battery.
[0066] Comparative Example
[0067] Take 3 ml of 1.0 M LiTFSI in DME:DOL=1:1 vol% electrolyte as a comparative example, recorded as Bare.
[0068] Preparation of Li||Li symmetrical battery using Bare: Use CR2025 type electrode shell, both positive and negative electrodes are lithium sheets (diameter 11mm), and the diaphragm is made of polypropylene (diameter 19mm). 80μL Bare is dripped on the diaphragm, and the battery is assembled in the order of positive electrode shell-lithium sheet-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After assembly, pressurize and package to prepare Li||Li symmetrical battery.
[0069] Preparation of Li||Cu half-cell using Bare: Use CR2025 type electrode shell, the positive electrode is copper foil (diameter 11mm), the negative electrode is lithium sheet (diameter 11mm), and the separator is polypropylene (diameter 19mm). 80μL Bare is dripped on the separator, and the battery is assembled in the order of positive electrode shell-copper foil-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After the assembly is completed, pressurize and package to prepare the Li||Cu half-cell;
[0070] Preparation of Li||S full battery using Bare: Use CR2025 type electrode shell, the positive electrode is aluminum foil coated with sulfur (diameter 11mm), the negative electrode is lithium sheet (diameter 11mm), and the separator is polypropylene (diameter 19mm). 80μL Bare is dripped on the separator, and the battery is assembled in the order of positive electrode shell-positive electrode-diaphragm-electrolyte-lithium sheet-spring-gasket-negative electrode shell. After assembly, pressurize and package to prepare Li||S full battery.
[0071] Taking Example 1 as an example, the electrochemical performance of the prepared lithium metal battery was tested, and the instrument used for the test was LANDCT2001A tester (Wuhan Landian Electronics Co., Ltd.).
[0072] Li||Li symmetric battery was charged and discharged at a constant current density of 1 mA cm at 30 °C. -2 ~200mA cm -2 , with a surface capacity of 1 mAh cm -2 ~10mAh cm -2 .
[0073] Li||Cu half-cell was charged and discharged at a constant current density of 1 mA cm at 30 °C. -2 , with a surface capacity of 1 mAh cm -2 ~2mAh cm -2 , the cut-off voltage is 1V.
[0074] The Li||S full battery was subjected to rate charge and discharge tests at 30°C with a test rate of 0.1C to 5C.
[0075] Figure 1 The Li||Li symmetric battery assembled in Example 1 and Comparative Example was -2 , surface capacity is 1 mAh cm -2Cycling performance diagram under the above test conditions. Under the above test conditions, the cycle life of the symmetrical battery assembled with the blank electrolyte of the comparative example is only 650 hours, while the symmetrical battery assembled with the modified electrolyte of Example 1 using ECAB concentration of 5mmol / L can be stably cycled for 2600 hours, which increases the cycle life of the lithium negative electrode by 4 times, indicating that the presence of the additive greatly improves the long-cycle stability of the lithium negative electrode.
[0076] Figure 2 The Li||Li symmetric battery assembled in Example 1 and Comparative Example was tested at a current density of 5 mA cm -2 , surface capacity is 5mAh cm -2 Cycling performance diagram under the above test conditions. Under the above test conditions, the symmetrical battery assembled with the blank electrolyte in the comparative example cannot be charged and discharged normally, while the symmetrical battery assembled with the modified electrolyte in Example 1 with an ECAB concentration of 5 mmol / L can be stably cycled for 1800 hours, which indicates that the presence of the additive greatly improves the long-cycle stability of the lithium negative electrode.
[0077] Figure 3 The Li||Li symmetric battery assembled in the comparative example of Example 1 was -2 , with a surface capacity of 10 mAh cm -2 Cycling performance diagram under the above test conditions. Under the above test conditions, the symmetrical battery assembled with the blank electrolyte in the comparative example cannot be charged and discharged normally, while the symmetrical battery assembled with the modified electrolyte in Example 1 with an ECAB concentration of 5 mmol / L can be stably cycled for 700 hours, which indicates that the presence of the additive greatly improves the long-cycle stability of the lithium negative electrode.
[0078] Figure 4 The Li||Li symmetric battery assembled in Example 1 and the comparative example was charged at a current density of 100 mA cm -2 , surface capacity is 1 mAh cm -2 The symmetrical battery assembled with the blank electrolyte in the comparative example can stably cycle for 10 hours, while the symmetrical battery assembled with the modified electrolyte in Example 1 with an ECAB concentration of 5 mmol / L can stably cycle for 45 hours, which increases the cycle life of the lithium negative electrode by 4.5 times, indicating that the presence of the additive greatly improves the long-cycle stability of the lithium negative electrode.
[0079] Figure 5 The rate performance diagram of the Li||Li symmetric battery assembled in Example 1 and the comparative example. The fixed surface capacity is 1 mAh cm -2 , at 1mA cm -2 Up to 200mA cm -2The current density was changed within a range to explore the comparison of the rate performance of the symmetrical cells assembled before and after the use of 5mmol / L ECAB. As shown in the figure, the symmetrical cell assembled in Example 1 using the modified electrolyte of 5mmol / L ECAB exhibited a lower polarization voltage and stable cycle performance, which was better than the symmetrical cell assembled in the comparative example using the blank electrolyte. This shows that the presence of the additive can make the lithium negative electrode have a lower cycle overpotential and higher cycle stability under fluctuating current density.
[0080] Figure 6 The SEM images of the surface and side of the lithium negative electrode of the Li||Li symmetric battery assembled in the comparative example and Example 1 after cycling. -2 , with a surface capacity of 1 mAh cm -2 After cycling for 400 hours under the test conditions, it can be seen from the figure that, under the same magnification, a large number of dendrites grow on the surface of the lithium negative electrode in the comparative example. In obvious contrast, the surface of the negative electrode of Example 1 is smoother, with almost no slender lithium dendrites. From the side SEM image, it can be seen that the comparative example produces dendrites about 207μm thick, while Example 1 only produces dendrites 131μm thick, indicating that ECAB as an additive can inhibit dendrites and make their growth more dense, which has a significant effect on inhibiting the growth of dendrites.
[0081] Figure 7 The Coulomb efficiency diagram of the Li||Cu half-cell assembled in Example 1 and the comparative example is shown in the figure. -2 , with a surface capacity of 1 mAh cm -2 Under the test conditions, the comparative example assembled using the comparative example showed a sudden drop in coulombic efficiency after 40 deposition / stripping cycles, which was attributed to the short circuit caused by dendrite growth during the cycle, which reduced the coulombic efficiency. However, the Li||Cu half-cell assembled using the modified electrolyte of 5mmol / LECAB in Example 1 can be stably cycled for more than 230 weeks, and the average coulombic efficiency is higher than 90%, which shows that the addition of ECAB can effectively inhibit the formation of lithium dendrites, thereby improving the Li 2+ Reversibility of deposition / stripping improves Coulombic efficiency.
[0082] Figure 8 The LiS battery cycle performance diagram of the Li||S full battery at 1C rate in Example 1 and the comparative example. As shown in the figure, when the battery is cycled to 450 cycles, the LiS battery assembled with the modified electrolyte of 5 mmol / L ECAB in Example 1 shows a higher capacity, indicating that the presence of the additive can improve the capacity and capacity retention rate of the lithium metal battery, and at the same time has a better cycle efficiency.
[0083] Fig. 9The figure is a full battery rate performance diagram of the Li||S full battery in Example 1 and the comparative example, with the charge and discharge rate varying in the range of 0.1C-5C. As shown in the figure, the LiS battery assembled in Example 1 using the modified electrolyte of 5mmol / L ECAB exhibits higher specific capacity and longer cycle life, which is better than the LiS battery assembled in the comparative example using the blank electrolyte. This shows that the presence of the additive can improve the specific capacity of the lithium metal battery and extend the cycle life of the battery.
[0084] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte for a lithium metal battery, characterized in that: The electrolyte includes an organic solvent, a soluble lithium salt and an additive; The additive is at least one of ethylene alkenyl (R2 alkyl ammonium fluoride), ethylene alkyne (R3 alkyl ammonium fluoride), ethylene alkenyl (R4 alkyl ammonium chloride), ethylene alkyne (R5 alkyl ammonium chloride), ethylene alkenyl (R6 alkyl ammonium bromide), ethylene alkyne (R7 alkyl ammonium bromide), ethylene alkenyl (R8 alkyl ammonium iodide), and ethylene alkyne (R9 alkyl ammonium iodide); The R alkyl group corresponds to a hydrocarbon group having 1 to 30 carbon atoms.
2. The electrolyte for lithium metal battery according to claim 1, characterized in that: The optimal carbon number of the R alkyl group is 16-20.
3. The electrolyte for lithium metal battery according to claim 1, characterized in that: The structural formula of ethylene alkyl (R alkyl ammonium fluoride) is: The structural formula of ethylene alkynyl (R alkyl ammonium fluoride) is: The structural formula of ethylene (R alkyl ammonium chloride) is: The structural formula of ethylene alkynyl (R alkyl ammonium chloride) is: The structural formula of ethylene alkyl ammonium bromide is: The structural formula of ethylene alkynyl (R alkyl ammonium bromide) is: The structural formula of ethylene alkyl (R alkyl ammonium iodide) is: The structural formula of ethylene alkynyl (R alkyl ammonium iodide) is: Wherein, R is a hydrocarbon group having 1 to 30 carbon atoms.
4. The electrolyte for lithium metal battery according to claim 1, characterized in that: The organic solvent is at least one of 1,3-dioxolane, ethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate and ethyl butyrate.
5. The electrolyte for lithium metal battery according to claim 1, characterized in that: The soluble lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium bis(oxalatoborate).
6. The electrolyte for lithium metal battery according to claim 1, characterized in that: In the electrolyte, the molar concentration of soluble lithium salt is 1 mol / L; In the electrolyte, the molar concentration of the additive is 1-20 mmol / L.
7. The electrolyte for lithium metal battery according to claim 1, characterized in that: In the electrolyte, the optimal molar concentration of the additive is 1-5mmol / L.
8. A method for preparing an electrolyte for a lithium metal battery, characterized in that: An organic solvent, a soluble lithium salt and an additive are mixed to obtain an electrolyte.
9. An application of an electrolyte for a lithium metal battery, characterized in that: The electrolyte is matched with a positive electrode, a negative electrode and a separator to assemble a lithium metal battery, and the obtained lithium metal battery has excellent cycle life and battery capacity.
10. The use of an electrolyte for a lithium metal battery according to claim 9, characterized in that: The negative electrode is a lithium sheet, lithium foil or lithium powder, and the thickness of the lithium sheet is 0.5 mm; The positive electrode material is sulfur, LiCoO2, LiNiO2, LiMn2O4, LiFePO4 or lithium nickel manganese oxide; The membrane material is glass fiber, polyethylene or polypropylene.
Citation Information
Patent Citations
Anode slurry of lithium secondary battery, anode and battery including the same
CN101431155A
Electrolyte solution for lithium metal batteries
CN108539272A
Electrolyte additive, electrolyte and secondary battery
CN113394453A
Lithium metal negative electrode material as well as preparation method and application thereof
CN116130632A
Metal lithium battery electrolyte additive and electrolyte thereof
CN116470136A